Building Climate Resilient Agriculture in Caribbean Countries: Haiti - Hayman, Alicia (Inter-American Institute for Cooperation on Agriculture (IICA), 2023)
Haiti's per capita GDP is the lowest in Latin America and the Caribbean. Climate resilient agriculture (CRA) technologies face barriers to inclusion, such as limited access to credit and inadequate policy framework. Agroforestry is important for Haiti's emissions reduction targets, but faces barriers such as inadequate compensation and poorly developed markets. The agriculture sector in Haiti is a significant emitter of greenhouse gases. Combining on-farm and beyond the farmgate measures will reduce the carbon footprint of Haiti's agricultural sector and provide mitigation and adaptation co-benefits.